Implementation of Oversight Policy, Apparatus Competence and Organizational Culture and its Effect on Performance of Field Supervision Basic Education - Muhamad Nur; Khasan Effendy; M. Aries Djaenuri; Sampara Lukman (GoAcademica Research & Publishing, 2019)
Abstract The administration of government requires a way of maximizing government management to achieve good governance to realize the welfare of the people and constitute demands of the constitution at the Preamble of the fourth Alenia 1945 Constitution. Article 31 of the 1945 Constitution states that Education is the right of every citizen, and the government and regional government guarantees the implementation of the national education system by Law Number 20 of 2003. This research aims to examine and analyze the effect of the implementation of supervisory policies, apparatus competencies, and culture organization of supervision performance in the field of primary education. The method used in this research is quantitative with open and closed questionnaires. The results of this study indicate that the causality relationship partially or simultaneously between the Implementation of Supervision Policy, Apparatus Competency, and Bureaucratic Culture to the Supervision Performance of the Basic Education Sector is entirely